IGJR 1/2020: Housing crisis: How can we improve the situation for young people? - IF and FRFG (Intergenerational Justice Review)
The Intergenerational Justice Review (www.igjr.org) is a peer-reviewed English language journal, reflecting the current state of research on intergenerational justice. The IGJR publishes articles from humanities, social sciences, and international law. The journal is released biannually and employs a double-blind peer review process. Its editorial board consists of about 50 internationally renowned experts from ten different countries. IGJR is indexed under Directory of Open Access Journals (DOAJ).